Analysis of project communication on smart card implementation in XYZ Malaysian higher education - Lubis, Muharman; Abdulmana, Sahidan; Ahlan, Abdul Rahman (2011)
Project communication is the exchange of project-specific information with the emphasis on creating understanding between the sender and the receiver. It reflected simultaneously to be an indispensable tool to manage project resources systematically. Communication through coordination and cooperation are common approach used for project scheduling, planning and control while collaboration establish the concrete result. Therefore, communication still remained as the main connector above all. Poor communication skill can cause anger, misunderstandings, conflict and distance that eventually influence project process significantly and lead to project failures. Analysis study was conducted to the ‘hiatus’ smart card project implementation in XYZ Malaysian higher education with emphasize the point of communication as the important point should be considered without eliminating other knowledge management area which also important in succession of project. In addition, the analysis study conducted to give limelight specifically towards the smart card implementation in higher education as the reference of other project in preventing project failure happen.